Carbon nanotubes for biomedical applications - Almeida, Mafalda R. (2024)
Carbon nanotubes (CNTs) were discovered in 1991, and since then, have been one of the most intensely studied nanomaterials due to their improved functionalities and diversity of applications. Specifically, CNTs are entirely composed of carbon atoms connected through sp2 bonds structured in several condensed benzene rings rolled up into a cylinder form. Depending on the number of graphitic layers, CNTs can be classified into single-walled carbon nanotubes (SWCNTs) or multi-walled carbon nanotubes (MWCNTs). The specific structural properties of CNTs, leading to a strong loading capacity, high surface area, high strength, and enhanced chemical and thermal stability, make these nanomaterials very promising for biomedical applications. In this sense, this book chapter overviews the potential applications of CNTs in the biomedical field, highlighting their usage on: (1) diagnosis, by the development of CNTs-based biosensors and imaging methods; (2) tissue engineering; (3) delivery systems of several anticancer and antihypertensive drugs, corticosteroids, genes, nucleic acids, among others; and (4) target therapies, namely photothermal and photodynamic therapies. Additionally, particular attention is given to the CNTs potential toxicity and different strategies to overcome this controversial subject, namely by the adequate CNTs functionalization.